Handbook of special education - Kauffman, James M.; Hallahan, Daniel P., 1944- (New York : Routledge, 2011)
Special education is now an established part of public education in the United States--by law and by custom. However, it is still widely misunderstood and continues to be dogged by controversies related to such things as categorization, grouping, assessment, placement, funding, instruction, and a variety of legal issues. The purpose of this 13-part, 57-chapter handbook is to help profile and bring greater clarity to this sprawling and growing field. To ensure consistency across the volume, chapter authors review and integrate existing research, identifying strengths and weaknesses, note gaps in the literature, and discuss implications for practice and future research. This book is an appropriate reference volume for anyone (researchers, scholars, graduate students, practitioners, policy makers, and parents) interested in the state of special education today: its research base, current issues and practices, and future trends. It is also appropriate as a textbook for graduate level courses in special eduction.
Section IX. Transition to adulthood and high incidence disabilities / section editor, David Scanlon -- Transition to postsecondary education / Joseph W. Madaus, Manju Banerjee, and Deborah Merchant -- Career choice patterns and behaviors of work-bound youth with high incidence disabilities / Jay W. Rojewski and Noel Gregg -- Transition to daily living for persons with high incidence disabilities / David Scanlon, James R. Patton, and Marshall Raskind -- Section X. Transition of students with low incidence disabilities / section editor, M. Sherril Moon -- Preparing students with low incidence disabilities to work in community / Katherine J. Inge and M. Sherril Moon -- Preparing students with low incidence disabilities for community living opportunities / Jane M. Everson and Meghan H. Trowbridge -- Section XI. Parent and family issues in special education / section editor, George H. S. Singer -- Evolution of the parent movement: past, present, and future / H. Rutherford Turnbull, III, Karrie A Shogren, and Ann P. Turnbull -- Resilience in families of children with disabilities: risk and protective factors / George H. S. Singer, ... [et al.] -- Promoting family outcomes in early intervention / Donald B. Bailey, Jr., ... [et al.] -- Section XII. Early identification and intervention in exceptionality / section editor, Maureen A. Conroy -- Advances in theory, assessment, and intervention with infants and toddlers with disabilities / Carl J. Dunst -- Early intervention and prevention of disability: preschoolers / Kathleen J. Marshall, ... [et al.] -- Frameworks for guiding program focus and practices in early intervention / Patricia A. Snyder, Tara W. McLaughlin, and Maria K. Denney -- Early identification and intervention in gifted education: developing talent in diverse learners / Catherine M. Brighton and Jane M. Jarvis -- Section XIII. Cultural and international issues in special education / section editor, Dimitris Anastasiou -- Ethnicity and exceptionality / Dimitri Anastasiou, Ralph Gardner, III, and Domna Michail -- Gender and exceptionality / Martha J. Coutinho and Donald P. Oswald -- International differences in provision for exceptional learners / Dimitris Anastasiou and Clayton Keller.
Includes bibliographical references and index.
Keywords: Special education -- United States -- Handbooks, manuals, etc; obrazovanje osoba s posebnim potrebama